Manajemen Kelompok Sadar Wisata Dalam Pengembangan Wisata Bukit Pangonan Indah di Desa Karang Gintung Kabupaten Banyumas: Management of Tourism Awareness Groups in the Development of Pangonan Indah Hill Tourism in Karang Gintung Village, Banyumas Regency - Hidayat, Arman; Sutikno, Chamid; Pribadi, Indah Ayu Permana; Amanda, Ariesta; Milata, Chanifia Izza (Institut Agama Islam Sunan Giri Ponorogo, 2025)
This study examines the management of the Tourism Awareness Group (Pokdarwis) in developing the Bukit Pangonan Indah tourist attraction in Karanggintung Village, Kemranjen Sub-district, Banyumas Regency. Using a descriptive qualitative research method, this study aims to analyze the application of George R. Terry’s management principles—planning, organizing, implementing, and controlling—in the management of community-based tourism destinations. (1) Planning focused on creating a master plan that includes infrastructure development, such as flower gardens and trekking paths, to enhance local wisdom-based tourism potential. (2) Organizing involved establishing a clear work structure that includes the village government, BUMDes, Pokdarwis, and the community. (3) Implementation covered digital promotion, MSME empowerment, and the construction of tourism facilities as planned. (4) Monitoring was conducted through annual evaluations, financial reporting, and visitor satisfaction surveys to improve service quality and tourist appeal. In conclusion, the management of Bukit Pangonan Indah has contributed to the Village’s Own-Source Revenue (PADes), although not yet maximized. Recommendations include enhancing promotion efforts, diversifying tourism attractions, and strengthening stakeholder collaboration to ensure inclusive and sustainable tourism development.